KORELASI ANTARA KADAR MAGNESIUM DENGAN RESISTENSI INSULIN PADA PENDUDUK SUKU BALI DI DESA PEDAWA KABUPATEN BULELENG - Sri Yenny, Luh Gede; Suastika, Ketut (journal of internal medicine, 2011)
Magnesium is one of microminerals playing pivotal role in glucose homeostasis and insulin activities. Magnesium playsa very important role in phosphorylation of insulin receptor. This is an analytical cross-sectional study to determinethe prevalence of hypomagnesium and correlation between magnesium level with insulin resistance, performed inPedawa Village Bali at February 2010. Subjects for this study were comprised of 111 people, 45 males (40.5%) and 66females (59.5%). Prevalence of hypomagnesium is 17.12%. The prevalence of hypomagnesium is higher in geriatricsubjects compare with non geriatric subjects (38.48% vs 10.98%, p = 0.004), is higher in diabetes subjects compare withnon diabetes (60% vs 15.1%, p = 0.035), and higher in subject with metabolic syndrome compare with non metabolicsyndrome (34.78% vs 12.5%, p = 0.025). Because lack on sensitivity of insulin measurement, 87 subjects (78.38%) thathave insulin level < 2  IU/ml can not measured by machine so the level of HOMA-IR of this subjects can not calculated,and just 24 subjects (21.62%) have insulin level > 2  IU/ml which can measured. From this 24 subjects, there is nosigniÞ cant correlation between magnesium level and insulin resistance (HOMA-IR) (r = -0.1, p = 0.642). In this study,we found a high prevalence of hypomagnesium in residents of Pedawa Village. The prevalence of hypomagnesium ishigher in geriatrics, diabetes mellitus, and metabolic syndrome subjects. There is no signiÞ cant correlation betweenmagnesium and insulin resistance (HOMA-IR), may be because lack of subject in this study. Thus further studies withhigher sensitivity of insulin measurement and enough sample of diabetic or metabolic syndrome patients in hospitalsettingare needed to determine correlation between magnesium level and insulin resistance.